Social Media Marketing and Participation Decision in Sport Run Events: A Self-Determination Theory Perspective - Farieq Fadloli; Lilik Wahyudi (Indonesian Journal of Sport Management, 2025)
The rapid growth of sport tourism, particularly in running events, has positioned social media as a primary platform for digital promotion and participant engagement. However, limited research has examined how the dimensions of social media marketing—content quality, interactivity, and influencer credibility—simultaneously influence participants’ motivation and trust within the context of sport tourism. This study aims to analyze the effects of these dimensions on participation decisions in running events, using Self-Determination Theory as the theoretical framework. The research employed a quantitative explanatory approach involving 303 active social media users who had participated in or planned to join running events such as the Jakarta Marathon, Borobudur Marathon, and Bali Marathon. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SmartPLS 4). The results indicate that content quality significantly influences motivation, while interactivity and influencer credibility have significant effects on trust. Both motivation and trust positively influence participation decisions and serve as mediating variables between social media marketing and behavioral intention. Conversely, content and interactivity do not have direct effects on participation decisions. This study emphasizes that effective digital marketing strategies in sport tourism should integrate emotional content, interactive communication, and credible influencers to strengthen participants’ intrinsic motivation and trust. Keywords: social media marketing, content, interactivity, influencer, motivation, trust, sport tourism, and participation decision